2001
DOI: 10.1080/02699050010007515
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of temperature in head injury

Abstract: It has been shown in a previous study that head injured patients appear to have a circadian rhythm of their body functions. This needed to be confirmed using additional data, better collection methods and analysis. Additional goals were to develop a method of detrending of physiological time series in order to improve rhythm detection when it may be hidden behind a low frequency trend and the creation of a computer system for data acquisition and analysis. The temperature data of 10 head injured patients was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…Brain damage can lead to disturbances in cerebral circadian rhythms, which was demonstrated using temperature sensors implanted in the brain parenchyma. A better outcome was shown in patients with preserved circadian rhythm and higher mesor (mean level) values, [ 6 , 7 ] which coincides with another study with similar results in half of the patients after severe traumatic brain injury (TBI) with maintained circadian rhythm of cerebral and body temperature [ 8 , 9 ]. These studies emphasize the importance of circadian rhythms, the presence of which reflects the higher potential of one’s own reparative responses.…”
Section: Introductionsupporting
confidence: 80%
“…Brain damage can lead to disturbances in cerebral circadian rhythms, which was demonstrated using temperature sensors implanted in the brain parenchyma. A better outcome was shown in patients with preserved circadian rhythm and higher mesor (mean level) values, [ 6 , 7 ] which coincides with another study with similar results in half of the patients after severe traumatic brain injury (TBI) with maintained circadian rhythm of cerebral and body temperature [ 8 , 9 ]. These studies emphasize the importance of circadian rhythms, the presence of which reflects the higher potential of one’s own reparative responses.…”
Section: Introductionsupporting
confidence: 80%
“…Cosinor analysis was strictly performed a 24-h intervals in this study, which is the most commonly used model for describing rhythmic temperature patterns. Studies involving brain injury patients support a period OR Odds ratio, CI confidence interval *p \ 0.05, **p \ 0.01 a Functional outcome, defined as unfavorable/favorable ratio, with favorable outcome defined as mRS score 0-2 at 12 months after surgery, and unfavorable outcome as mRS score 3-6 at 12 months after surgery b Survival outcome, defined as the alive/dead ratio, was followed up at 12 months after surgery c Intact rhythm of BT was defined as fitting the p value of the cosinor analysis (p \ 0.05) for brain temperature of approximately 24 h for body temperature and BP assessment [38][39][40]. Our study identified a mesor [ 37.5 °C in 66.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cosinor analysis was strictly performed a 24-h intervals in this study, which is the most commonly used model for describing rhythmic temperature patterns. Studies involving brain injury patients support a period of approximately 24 h for body temperature and BP assessment [ 38 – 40 ]. Our study identified a mesor > 37.5 °C in 66.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 24-h fixed period cosinor is the most commonly used and interpretable model to describe diurnal temperature patterns in adults and is well established as an effective model for this purpose. Studies of mixed brain injury and intensive care patients support that a period of approximately 24 h is present in this group of patients [21][22][23][24][25][26]. The 24-h fixed model should thus be useful to identify overt 24-h temperature pattern disruptions that might occur as a result of brain insult and the impact of medical care, nursing care, and the intensive care clinical environment.…”
Section: Discussionmentioning
confidence: 99%